Family ties and written multilingual heritage of the Frankapani at the dawn of the early modern period - Jurković, Ivan, povjesničar (Array, 2020)
In the second half of the fifteenth and the first half of the sixteenth century the Frankapani of Krk, Senj, and Modruš were at the peak of their power. This family of Croatian counts was networked through marriage from the Adriatic to the Baltic Sea with Italian, Hungarian, Austrian, and German royal and aristocratic families. Their presence in the courts of their next of kin, as well as their in-laws, is therefore not surprising, whether it be the Roman Curia or the Hohenzollern Branderburger Palace in Berlin. In such a wide system of communications, the Frankapani presented themselves to the European public as a multilingual family ready to promulgate not only the written heritage nurtured during the Middle Ages in Croatia (Latin and Glagolitic), but also ready to adopt, promote, and disseminate the written heritage of their spouses (Italian, German, Hungarian). The following examples attest to this statement: the Roman breviary translated into the German language by Christopher Frankapan and his wife Apollonia Lang printed in 1518 in Venice, the anti-Turkish speech in Latin delivered by Christopher’s father, Bernardin, before the German assembly in Nuremberg and printed in 1522 for the occasion, the translated epistles of Saint Paul, from Latin to Hungarian, donated by Catherine Frankapan married to Gabriel (Gábor) Perényi, printed in Krakow in 1533, and the first Croatian- language breviary written in the Latin script, rather than in the Glagolitic, commissioned by Catherine Frankapan married to Nicholas Zrinski, published in 1560 in Padua.